The Governor of Michoacán and the University Conflict of 1949. The Vision of Nemesio García Naranjo - García naranjo, Francisco Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article analyzes texts written by the journalist Nemesio García Naranjo, which discussed the events unleashed between the 28 of July and the 26 of August of 1949 in Morelia, Michoacán (Mexico), in a confrontation between the students and authorities of Universidad Michoacana de San Nicolás de Hidalgo, and the State Governor, Jose María Mendoza Pardo, a member of the governing party. The conflict was detonated by the death of two university students in the hands of the army. This event triggered marches and university strikes in the whole country, putting the governability of the state of Michoacán into crisis.The journalistic corpus written by García Naranjo is analyzed in two directions. On the one hand, it emphasizes the liberal position with which this author examined the events and their social and political repercussions for the regime. This ideological positioning contravenes the wrong place in which historiography has put this character: as part of the reactionary and antirevolutionary right. On the other hand, in demostrating that this journalist exhibited a way of thinking proper to the ´liberal right´, we also establish that he judged the events of Morelia and the role of Universidad Michoacana from this perspective, demostrating a dissonant voice in a scenario dominated by ideological biases and political interests, which unanimously accused “the communist conspiracy” as responsable agent.